’Adaptive Authoritarianism’ in Contemporary China: Identifying Zones o f Legitimacy Building - Ahlers, Anna Lisa; Schubert, Gunter (Reviving Legitimacy: Lessons for and from China, 2011)
Anna L. Ahlers and Gunter Schubert, ’Adaptive Authoritarianism’ in Con temporary China: Identifying Zones of Legitimacy Building, in: Deng Zh englai and Guo Sujian (eds), Reviving Legitimacy: Lessons for and from China, Lanham: Lexington Books (2011),